2021
DOI: 10.21608/mjae.2021.88860.1038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Opaque Photovoltaic Shading on Microclimate and Growth of Strawberry in Greenhouses

Abstract: The effect of photovoltaic PV panels on strawberry growth and the greenhouse microclimate has been studied meanwhile; the annually generated electric energies were estimated by the PolySun program. The peak power of the opaque PV was 310 W. There were four PV panels distributed on the top of greenhouse south plastic roof at a vertical distance of 0.08 m as an isolated air layer under the PV panels at a tilt angle of 30 ͦ . Meanwhile at a horizontal distance between panels of 1.1 m to allow the solar light ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…There were no significant differences between the two production systems on leaf chlorophyll reading in both seasons. These results are in agreement with those of Hassanien and Li (2021). Plants produced from plastic house had larger leaf area than those produced from open field; however, the difference was significant in the first season only.…”
Section: Effect Of Production Systems Cultivars and Their Interaction...supporting
confidence: 91%
See 2 more Smart Citations
“…There were no significant differences between the two production systems on leaf chlorophyll reading in both seasons. These results are in agreement with those of Hassanien and Li (2021). Plants produced from plastic house had larger leaf area than those produced from open field; however, the difference was significant in the first season only.…”
Section: Effect Of Production Systems Cultivars and Their Interaction...supporting
confidence: 91%
“…Similarly, DeGannes et al (2014) and Aied et al (2017) revealed that the high temperature in the greenhouse increases leaf size and leaf expansion. It was reported by Hassanien and Li (2021) that the average leaf area of the shaded strawberry plants by PV was significantly higher than that of the unshaded plants. The eggplant plants increase their height, leaf area and leaf arrangement in order to maximize their exposure to light (Aied et al, 2017).…”
Section: Effect Of Production Systems Cultivars and Their Interaction...mentioning
confidence: 82%
See 1 more Smart Citation
“…The onset of flowering is not affected by light intensity [ 35 ], which was confirmed in the present study, with the onset of flowering being the same in both crop lines regardless of the shading amount. In previous studies, the shading did not affect the number of flowers for pepper plants [ 37 ] and strawberry plants [ 38 ]. However, in our results, the number of flowers for each crop line was lower compared to the other, after a preceding period of increasing shading.…”
Section: Discussionmentioning
confidence: 95%